STUDI FENOMENOLOGI DAMPAK PENDIDIKAN AGAMA KRISTEN TERHADAP PERGESERAN GELAR KEBANGSAWANAN DI SUMBA TIMUR - Trijuliani Renda (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
Phenomenological Study of the Impact of Christian Education on Shifting Nobility in East Sumba, Trijuliani Renda, M.Si. Kupang State Christian Institute. The research aims to describe 1) the model of Christian Religious Education in Sumbanese culture, 2) the form of degree shift in social stratification in East Sumba, and 3) the impact of Christian religious education on the shift in the nobility of the Sumbanese people in social, political and economic life. The method used in this research is qualitative. This research was taken using observation, in-depth interviews and documentation review. The results of the study prove that the Christian religious education model respects the context and is centered on Christ. The form of the title shift is evolutive when viewed from the perspective of modern society but becomes chaos for indigenous peoples. The impact in social life is the creation of Christian spiritual values in society. Political Impact there is the term political axis/political maramba/nobels for those who have positions in government so that the community without limits pursues every achievement in life including politics, while the economic impact of the creation of a modern society with local packaging so that nobles are equated with ownership of goods and services. There was a title shift in East Sumba and this title shift towards a positive direction where through Christian religious education everyone is touched without limits to push up every stage to be achieved for freedom and equality.